Characterization of CD66b and its relationship between immune checkpoints and their synergistic impact in the prognosis of surgically resected lung adenocarcinoma. (October 2021) - Shen, Mingjing; Jiang, Kanqiu; Sui, Yiqun; Xu, Zhonghua; Cui, Hongxia; Wang, Youyou; Zhang, Huan; Xu, Zhonghen; Xu, Weihua; Ding, Qifeng; Chen, Yongbing
Highlights: CD66b + TINs were significantly associated with immune checkpoints including LAG-3, PD-1, CTLA-4, TIM-3, TIGIT and PD-L1. CD66b + TINs were significantly associated with poor prognosis. A combination of CD66b and LAG-3 could further stratify patients into different groups with distinct prognoses. Abstract: Objectives: CD66b positive tumor-infiltrating neutrophils (TINs) are key immunity cells in the tumor microenvironment (TME). However, their relationship with clinicopathological features, immune checkpoints (ICs), and prognostic value remains undetermined in lung adenocarcinoma (LUAD). In this study, we aimed to characterize the infiltration by TINs and the prognostic significance in patients with surgically resected LUAD. Materials and methods: Expression of CD66b and ICs, including PD-L1, PD-1, CTLA4, LAG3, TIM3, TIGIT, VISTA, and BTLA, in both cancer cell and tumor-infiltrating lymphocytes (TILs) were estimated by immunohistochemistry in resected LUAD. The associations between CD66b expression and clinicopathological characteristics in patient prognoses were analyzed. We also verified results in another cohort from 85 patients with untreated LUAD and further analyzed the correlation between CD66b expression and EGFR and KRAS mutation status in addition to the rearrangement of the anaplastic lymphoma receptor tyrosine kinase gene (ALK). Results: A total of 240 patients were included in this study. CD66b expression was observed in 87 (36.2%) samples. ICs including PD-L1, PD-1, CTLA4, LAG3, TIM3, TIGIT, VISTA, and BTLA were observed in percentages that ranged from 23.8% to 59.4%. Positive CD66b expression significantly correlated with smoking history ( p = 0.029), pathological stage ( p = 0.040), and the positive expression of LAG-3 ( p < 0.001), PD-1 ( p = 0.008), CTLA-4 ( p = 0.013), TIM-3 ( p = 0.025), TIGIT ( p = 0.002), PD-L1 in TILs ( p = 0.015), and PD-L1 in tumor cells ( p = 0.010). CD66b positivity was significantly associated with worse recurrence-free survival (RFS) (hazard ratio, HR, 1.687; 95% confidence interval, CI, 1.058–2.690, p = 0.028) and overall survival (OS) (HR, 1.667; 95% CI, 1.097–2.534, p = 0.017). Subgroup analysis revealed that the CD66b+/LAG-3 + group had the worst RFS (5-year rate: 39.5%, ) and OS (5-year rate: 53.7%, ), while the CD66b−/LAG-3 − group had the best RFS (5-year rate: 65.6%) and OS (5-year rate: 78.8%). The p value in analysis of RFS and OS was 0.005 and 0.008, respectively. In the verification set, high expression of CD66b was also significantly correlated with the positive expression of LAG-3 ( p < 0.001), PD-1 ( p = 0.002), CTLA-4 ( p = 0.034), TIM-3 ( p = 0.049), PD-L1 in TILs ( p = 0.003), and PD-L1 in tumor cells ( p = 0.045). There was no correlation between CD66b expression and positive TIGIT expression ( p = 0.077), EGFR mutation ( p = 0.223), KRAS mutation ( p = 0.151), and ALK fusion ( p = 0.310). Conclusion: CD66b had a relatively high positive expression rate and special clinicopathological features in patients with LUAD. CD66b + TINs were related to the expression of ICs and associated with poor prognoses in LUAD. A combination of CD66b and ICs, especially LAG-3 could further stratify patients into different groups with distinct prognoses.